INTERNET OF THINGS (IOT) BASED ADVANCED ONLINE EXAMINATION USING RASPBERRY PI - Pawar, Kunal.S.; Latane, Pravin.C. (International Journal of Research -GRANTHAALAYAH, 2018)
With the development in the education system, considering the latest current online exam system, a new projection of online exam system based on Raspberry pi IOT is proposed, and the key implementation techniques and methods are also described. The growing ubiquity of wireless, RFID mobile and sensor devices has provide a promising opportunity to build the powerful examination systems and applications by Internet of Things (IoT). A wide range of IoT applications have been developed in recent years. In an effort to understand the development of IoT in online examination, here we propose the current research of IoT, IOT key enabling technologies, major IoT applications in online examination and identifies research trends and challenges. Here we initially all the examine details are stored in the server. Then By applying face recognition (in Open CV based) technique, you can start the online examination. Due to sometime unwanted person also enter to wright the exam, so this is the best way to identified any culprits are found or not.